Dual‐Targeting Lactoferrin‐Conjugated Polymerized Magnetic Polydiacetylene‐Assembled Nanocarriers with Self‐Responsive Fluorescence/Magnetic Resonance Imaging for In Vivo Brain Tumor Therapy. Issue 6 (28th January 2016) - Fang, Jen‐Hung; Chiu, Tsung‐Lang; Huang, Wei‐Chen; Lai, Yen‐Ho; Hu, Shang‐Hsiu; Chen, You‐Yin; Chen, San‐Yuan
Abstract : Maintaining a high concentration of therapeutic agents in the brain is difficult due to the restrictions of the blood–brain barrier (BBB) and rapid removal from blood circulation. To enable controlled drug release and enhance the blood–brain barrier (BBB)‐crossing efficiency for brain tumor therapy, a new dual‐targeting magnetic polydiacetylene nanocarriers (PDNCs) delivery system modified with lactoferrin (Lf) is developed. The PDNCs are synthesized using the ultraviolet (UV) cross‐linkable 10, 12‐pentacosadiynoic acid (PCDA) monomers through spontaneous assembling onto the surface of superparamagnetic iron oxide (SPIO) nanoparticles to form micelles‐polymerized structures. The results demonstrate that PDNCs will reduce the drug leakage and further control the drug release, and display self‐responsive fluorescence upon intracellular uptake for cell trafficking and imaging‐guided tumor treatment. The magnetic Lf‐modified PDNCs with magnetic resonance imaging (MRI) and dual‐targeting ability can enhance the transportation of the PDNCs across the BBB for tracking and targeting gliomas. An enhanced therapeutic efficiency can be obtained using Lf‐ Cur (Curcumin)‐PDNCs by improving the retention time of the encapsulated Cur and producing fourfold higher Cur amounts in the brain compared to free Cur . Animal studies also confirm that Lf targeting and controlled release act synergistically to significantly suppress tumors in orthotopic brain‐bearing rats. Abstract : Polymerized magnetic polydiacetylene nanocarriers (PDNCs) are developed with ultraviolet cross‐linkable 10, 12‐pentacosadiynoic acid (PCDA) micelles embedded with the superparamagnetic iron oxide nanoparticles (SPIOs) for magnetic resonance imaging (MRI) and sustained curcumin ( Cur ) release. To enhance the blood–brain barrier (BBB)‐crossing efficiency and brain tumor therapy, the lactoferrin (Lf)‐conjugated PDNCs are synthesized to achieve increased drug accumulation and half‐life in the brain tumors, substantially reducing the systemic drug concentrations and side effects.